An organisational change intervention for increasing the delivery of smoking cessation support in addiction treatment centres: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Bonevski, Billie; Guillaumier, Ashleigh; Shakeshaft, Anthony; Farrell, Michael; Tzelepis, Flora; Walsberger, Scott; D'Este, Catherine; Paul, Chris; Dunlop, Adrian; Searles, Andrew; Kelly, Peter; Fry, Rae; et al.
Abstract Background The provision of smoking cessation support in Australian drug and alcohol treatment services is sub-optimal. This study examines the cost-effectiveness of an organisational change intervention to reduce smoking amongst clients attending drug and alcohol treatment services. Methods/design A cluster-randomised controlled trial will be conducted with drug and alcohol treatment centres as the unit of randomisation. Biochemically verified (carbon monoxide by breath analysis) client 7-day-point prevalence of smoking cessation at 6 weeks will be the primary outcome measure. The study will be conducted in 33 drug and alcohol treatment services in four mainland states and territories of Australia: New South Wales, Australian Capital Territory, Queensland, and South Australia. Eligible services are those with ongoing client contact and that include pharmacotherapy services, withdrawal management services, residential rehabilitation, counselling services, and case management services. Eligible clients are those aged over 16 years who are attending their first of a number of expected visits, are self-reported current smokers, proficient in the English language, and do not have severe untreated mental illness as identified by the service staff. Control services will continue to provide usual care to the clients. Intervention group services will receive an organisational change intervention, including assistance in developing smoke-free policies, nomination of champions, staff training and educational client and service resources, and free nicotine replacement therapy in order to integrate smoking cessation support as part of usual client care. Discussion If effective, the organisational change intervention has clear potential for implementation as part of the standard care in drug and alcohol treatment centres. Trial registration Australian and New Zealand Clinical Trials Registry, ACTRN12615000204549 . Registered on 3 March 2015.